(3EOGQI GdLhOI (B: s (3ehLgI dWdHI GdSfI GdKGdKI djSGfS (BLMD (3bSe Ydhe GdJSjjQ (B/ s - (3bOjO, ahRjIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2021)
(3CSGSjGJ Mhd GdLhOI h EOGQJgG , GdGWGQ GdfXQj dGOGQI GdLhOI GdTGdI , JWHjb EOGQI GdLhOI GdTGedI , COhGJ EOGQI GdLhOI GdTGedI , fXGe EOGQI GdLhOI GdGjRh (B9000 (3, adSaI GdSJI SjLeG h MdbGJ GdLhOI , JcGdja GdLOhI , EOGQI GdehGQO GdHTQjI h EOGQI GdLOhI GdTGedI , LhGFR GdLhOI(B.s
(3eQGLY U(B.130s
Keywords: (3GdLhOIs; (3LhOI GdGfJGLs